APAC in Hungary - Tihanyi, Miklós (Magyar Rendészet, 2018)
The author examines the Hungarian features of the APAC units. Study visits were carried out in four correctional institutions and interviews with the chaplains were recorded. According to his conclusions we can find places in Hungary called APACs or religious units where the main element of the reintegration is religious education. The difference between the two kinds of units are not significant. Many of the features of the APAC methodology are partly or entirely missing from the Hungarian practice, though civilians are present but not to the extent they should be; also, there is a great difference regarding the quality of cooperation with them. There are significant handicaps in the selection and promotion system. They totally lack the progressive regime, the family support, and the legal help. The regulator gratuitously reduces the time that can be spent there to 3 years. In case of long sentences this time is not enough to counterweight the negative effect of prison life.